Gene doping: an overview and current implications for athletes - van der Gronde, T.; de Hon, O.; Haisma, H. J; Pieters, T. (British Journal of Sports Medicine, 2013)
The possibility of gene doping, defined as the transfer of nucleic acid sequences and/or the use of normal or genetically modified cells to enhance sport performance, is a real concern in sports medicine. The abuse of knowledge and techniques gained in the area of gene therapy is a form of doping, and is prohibited for competitive athletes. As yet there is no conclusive evidence that that gene doping has been practiced in sport. However, given that gene therapy techniques improve continuously, the likelihood of abuse will increase.